When does FDI have positive spillovers? Evidence from 17 emerging market economies - Yuriy Gorodnichenko; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2007)
We use firm-level data and national input-output tables from 17 countries over the 2002-2005 period to test new and existing hypotheses about the impact of foreign direct investment (FDI) on the efficiency of domestic firms in the host country (i.e., spillovers). Providing evidence from a larger sample of countries and greater variety of firms than existing studies, with separate estimates by firm size, age, and sector, we show: a) backward spillovers (stemming from supplying a foreign firm in the host country or exporting to a foreign firm) are consistently positive; b) horizontal spillovers are mostly insignificant but positive for older firms and firms in the service sector; d) forward spillovers (from purchasing from foreign firms or importing) are also positive only for old and service sector firms. We find no support for the hypothesis that spillovers are greater for FDI with more advanced technology. While efficiency of domestic firms' is affected by the business environment, the strength of FDI spillovers is not, either when measured by the degree of corruption, bureaucratic red tape or by differences across regions that vary in terms of development. Testing whether spillovers vary with the firm's absorptive capacity we find: i) distance from the efficiency frontier tends to dampen horizontal spillovers in manufacturing and backward spillovers among old firms; ii) whereas firms with a larger share of university educated workforce are more productive, they do not enjoy greater FDI spillovers than firms with less educated workers. FDI spillovers hence vary by sectors and types of firms.
Keywords: 330; FDI; spillovers; transition economies; efficiency; Direktinvestition; Unternehmensentwicklung; Spillover-Effekt; Aufstrebende Märkte; Transformationsstaaten